Implementasi Tanda Tangan Digital pada Surat Keterangan Bebas Laboratorium - Ferzha Putra Utama; Murfid Aqil; Hanan Raihana; Rizkianda Rahmansyah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
A laboratory-free letter is a document required by students of the Bengkulu University Information System Study Program on the way to graduation. During the current pandemic, the management of academic letters can cause crowds to spread the Covid-19 virus. The lack of awareness and knowledge of the academic community in the integrity and validity of a digital document causes a lot of use of signatures without proving their authenticity. A platform is needed to manage educational documents to avoid viruses and misuse of digital copies. This web-based system implements a QR Code generator to generate digital signatures. This applied research applies prototyping for its development method then tested for functionality and user acceptance. The test results show that 100% of the functions can run well, and user acceptance leads to a score of 80.